Estimation of the nutrient variation in feed delivery and effects on lactating dairy cattle - A.L. Carroll; K.J. Hanford; C. Abney-Schulte; P.J. Kononoff (JDS Communications)
Diets formulated for dairy cattle are designed to supply nutrients, but rations delivered to the animal may deviate from original formulations, resulting in implications for milk production, composition, and even pregnancy rate. The objective of this study was to evaluate retrospective feed mixing records collected from 8 commercial dairy farms over 52 wk. Farms ranged from 2,982 to 29,783 animals, producing 31.8 ± 5.93 (±SD) kg of milk with 4.14 ± 0.461% fat and 3.26 ± 0.218% protein. Data collected included daily TMR nutrient deviation, calculated as diet nutrient content minus the observed divided by the formulated diet concentrations of CP, fat, NDF, and starch. Data were analyzed with fixed effects of time (modeled as 28-d periods) and days of positive nutrient deviation in fat, CP, NDF, and starch with each nutrient alone and in combination with the other nutrients, random effects of herd, and repeated measure of time within herd. The nutrient deviation by farm averaged (±SD) 1.68 ± 2.655, 2.28 ± 4.473, 1.75 ± 2.621, and 1.47 ± 2.147% for CP, fat, NDF, and starch, respectively. Days of positive nutrient deviation per period averaged (±SD) 25.5 ± 3.47, 25.5 ± 3.72, 25.6 ± 3.49, and 25.9 ± 2.61, respectively. Dry matter intake (DMI; 17.2 ± 1.78 kg/d) decreased with increasing positive deviation days in starch (−0.0483 ± 0.01265) and increased with increasing positive deviation days in CP (0.0211 ± 0.00942). Milk yield (31.4 ± 2.50 kg/d) increased with positive deviation days in starch (0.0486 ± 0.02110) and decreased with increased positive deviation days in NDF (−0.0298 ± 0.02202). Finally, pregnancy rate (21.7 ± 4.34) increased with increasing positive deviation days in fat (0.385 ± 0.1635) and decreased with increasing positive deviation days in CP (−0.420 ± 0.1879). For these models, period significantly affected milk yield but was not observed to affect pregnancy rate and DMI. Results suggest farm and nutrient type were significant sources of variation, and overall, farms overfeed nutrients CP, fat, NDF, and starch 92% of the days of a 28-d period.